The representation of the climate crisis in Croatian online news media - Šarić, Ljiljana; Trnavac, Radoslava (Frontiers in Communication, 2026)
This study analyzes agency and news values across verbal and visual modalities in Croatian online news on the climate crisis, examining how climate change is portrayed. We explore newsworthiness, visual framing, and metaphor, linking agency to broader concerns about responsibility. In addition, the analysis traces how different types of agency shape news values in both metaphorical and non-metaphorical micro-contexts. To achieve our goals, we employ four theoretical frameworks: Halliday and Matthiessen’s Transitivity model; Conceptual Metaphor Theory as developed by Lakoff and Johnson and subsequently extended by Forceville, Steen et al., and Hart; Bednarek and Caple’s news values analysis framework; and the climate-change visual framing approach developed by O’Neill et al. The findings reveal a contradictory picture. Croatian online media primarily evoke worry, reinforced by the news values of Impact and Negativity and by frequent portrayals of humanity as the Goal in both texts and images. Metaphorical framings follow a clear pattern: individuals appear as victims facing stronger adversaries, while abstract entities such as the climate crisis and climate change are depicted as malevolent agents in a dominant war scenario. News stories rarely highlight initiatives that might foster a sense of agency. Most articles present climate change as a global problem and use images of places distant from, or only loosely related to, Croatia. The result is a narrative that feels remote and insufficiently relevant to the average reader.